EFFECTIVENESS AND EFFICIENCY OF MASSAGE THERAPY IN PAIN MANAGEMENT OF VAGINAL DELIVERY - Yuanita Wulandari (Jurnal Keperawatan Muhammadiyah, 2016)
Objective: to identify the effectiveness and efficiency of massage therapy in pain management of vaginal delivery. Methods: This article was review article which will review several article from several databased to answer the clinical question. The clinical question was “how is the effectiveness and efficiency of massage therapy for pain management during vaginal delivery process?. Advence search technique was used during searching the articles in Cochrane library, Ovid medline, EBSCO, and Pubmed. “Massage therapy or massage”,  “spontaneous or vaginal”, “delivery or labor or childbirth”, “pain management or pain manage”, “pain scale”,  “anxiety”,  and “family participation” was used as keywords to searching in those databased.  Results: four articles were found. However only three articles which suitable to answer the clinical question. The tittle of those articles were “Effects of massage on pain and anxiety during labour: a randomized controlled trial in Taiwan”, “Effect of massage therapy on severity of pain and outcome of labor in primipara”, and “Massage or music for pain relief in labour: A pilot randomised placebo controlled trial”. Conclusion: Massage therapy is more effective and efficiency reduces pain on stage 1 of vaginal delivery when combined with standard care (breathing therapy).